2012
DOI: 10.1111/rda.12114
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the First Service Conception Rate of Cows in Smallholder Dairy Farms in Bangladesh

Abstract: The successful outcome of an insemination is a combination of both male and female fertility-linked factors. We investigated the first service conception rate of cows at artificial insemination (AI) in the smallholder dairy farms in Bangladesh. Frozen straws were prepared from ejaculates of Bos indicus (n = 7) and Bos indicus × Bos taurus (n = 7) AI bulls. Fertility was determined from 6101 first services in cows that were performed by 18 technicians in four regions between April 2004 and March 2005. Pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 10 publications
3
24
1
Order By: Relevance
“…In this study, the first service conception rate ranged from 40.91% in Holstein dairy cows fed the control diet, and 44.44% in cows fed the ELS diet. This range is within the range of 26.7% to 50.7% reported by previous studies [47,48]. Our finding that the first-service conception rate of dairy cows did not alter depending on the experimental diets is consistent with previous studies that reported conception and pregnancy rates to be unchanged when diets were supplemented with linseed, saturated FA, or n-6 FA [41,49].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the first service conception rate ranged from 40.91% in Holstein dairy cows fed the control diet, and 44.44% in cows fed the ELS diet. This range is within the range of 26.7% to 50.7% reported by previous studies [47,48]. Our finding that the first-service conception rate of dairy cows did not alter depending on the experimental diets is consistent with previous studies that reported conception and pregnancy rates to be unchanged when diets were supplemented with linseed, saturated FA, or n-6 FA [41,49].…”
Section: Discussionsupporting
confidence: 92%
“…The AI number may affect CR; differences in CR between AI number groups have been reported in zebu cattle (Mollah, Gofur, Asaduzzaman, & Bhuiyan, ). In addition, other factors have been associated with CR in other beef cattle breeds and in dairy cattle, these include the following: age of heifers at first AI, parity, interval from calving to first AI, and AI season (Jeong, Choi, Kang, Hur, & Kim, ; Kruif, ; Kuhn, Hutchison, & Wiggans, ; Maufti, Alam, Sarker, Bostami, & Das, ; Sharifuzzaman, Barman, Matin, Rokonuzzaman, & Ashadul, ; Shiddiqui et al., ). Yet, there have been no studies investigating the effects of interactions between AI number and these other factors on CR in Japanese Black cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Haque et al (2015) recorded that the first service conception rate was higher in cows with 3-4 BCS than in cows with 1.5 -2 BCS values. Siddiqui et al (2013) found that in cows with BCS from 1.5 to 2.0 the conception rate from first service was lower than in cows with BCS from 2.5 to 3.5 in dairy cows. Santos (2008) suggested that the negative energy balance (NEB) reduces ovulatory cycle's recovery, oocyte and embryo quality and pregnancy establishment and maintenance in dairy cattle.…”
Section: Effect Of Body Condition Score At Calving On Number Of Servimentioning
confidence: 82%